GAMBARAN PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI PADA IBU HAMIL TRIMESTER III DI DESA PRENDENGAN KECAMATAN BANJARMANGU KABUPATEN BANJARNEGARA TAHUN 2010 - Amalia Dwi Feviana; Reni Dwi Setyaningsih; Ikit Netra Wirakhmi (Universitas Harapan Bangsa Purwokerto, 2011)
Indonesia Demographic Health Survey (IDHS) 2007, the maternal mortality rate (MMR) in Indonesia showed the number 228 / 100,000 live births. Planning program delivery andprevention of complications (P4K) is the latest program made by the government to help lowerAKI. One aspect that is assessed in P4K is birth attendant. In the village Prendengan non healthworkers maternity coverage in 2010 amounted to 63%. The purpose of research to describe theplanning and delivery of prevention kompliksi the third trimester pregnant women in ruraldistricts Prendengan Banjarmangu Banjarnegara district in 2010. Methods This study usedquantitative descriptive method with cross sectional approach and instrument is the checklist. Thesample 36 third trimester pregnant women in the village Prendengan. The results showedPlanning childbirth and prevention of complications in the third trimester pregnant women in thevillage Prendengan pretty good at 44% and 44% unfavorable. Planning for birth attendants88.9%, not 88.9% planned home delivery, planning perlenglengkapan complete maternal andinfant 88.9%, not 75% of the financial plan, no plan pendonordarah 91.7%, 80.6% do not plantransportation , planned a labor companion 100%, 100% decision makers planned, not plannedKB postpartum 66.7%. Overview delivery planning and prevention of complications in the thirdtrimester pregnant women in the village Prendengan with the results, please either 44% andunfavorable 44% Keywords: Planning childbirth and prevention of complications, third trimester pregnant women, behavior